2009
DOI: 10.1021/es803526g
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-Term Performance and Chromate Reduction Mechanisms in a Field Scale Permeable Reactive Barrier

Abstract: An innovative full-scale implementation of a permeable reactive barrier, consisting of a double-row of cylinders filled with zerovalent iron shavings, for chromate remediation was monitored over four years. Solid samples were analyzed to elucidate (i) the relevant corrosion mechanisms and products, (ii) the pathways of chromate reduction and immobilization, and (iii) the long-term performance of the barrier situated in a hydrological and geochemical complex groundwater regime. Sampling and analysis of groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 30 publications
1
44
0
1
Order By: Relevance
“…In addition, hematite, maghemite and lepidocrocite were also detected. While Cr VI was not detected, Cr III occurred in the form of two different (in terms of Cr/Fe ratio) mixed Cr III -Fe III hydroxides [60]. Based on these observations, the authors suggested following possible reaction pathways that may contribute to Cr VI removal: (1) heterogeneous reduction of Cr VI with Fe 0 ; (2) heterogeneous reduction of Cr VI with Fe II bearing solids; (3) homogeneous reduction of Cr VI with dissolved Fe II ; and (4) precipitation of the resulted Cr III as mixed Cr III -Fe III -hydroxides.…”
Section: Willisau (Switzerland)mentioning
confidence: 89%
See 4 more Smart Citations
“…In addition, hematite, maghemite and lepidocrocite were also detected. While Cr VI was not detected, Cr III occurred in the form of two different (in terms of Cr/Fe ratio) mixed Cr III -Fe III hydroxides [60]. Based on these observations, the authors suggested following possible reaction pathways that may contribute to Cr VI removal: (1) heterogeneous reduction of Cr VI with Fe 0 ; (2) heterogeneous reduction of Cr VI with Fe II bearing solids; (3) homogeneous reduction of Cr VI with dissolved Fe II ; and (4) precipitation of the resulted Cr III as mixed Cr III -Fe III -hydroxides.…”
Section: Willisau (Switzerland)mentioning
confidence: 89%
“…The occurrence of two different Cr III species at the surface of exhausted Fe 0 shavings strongly supports this conclusion: (1) Cr III -Fe III hydroxides with Cr/Fe ratio > 1/3, produced via heterogeneous reduction of Cr VI with Fe II bearing solids; and (2) Cr III -Fe III hydroxides with Cr/Fe ratio of about 1/3, resulted from the homogeneous reduction of Cr VI with dissolved Fe II . In addition, the existence of Cr III -Fe III hydroxides not only on Fe 0 shavings, but also on the surface of gravel particles, further suggested that the homogeneous reduction process with dissolved Fe II , occurring within the pores space, was a very important pathway [60]. Accordingly, one of the main limiting factors for the longevity of the PRB was found to be the availability and accessibility of Fe II [59].…”
Section: Willisau (Switzerland)mentioning
confidence: 99%
See 3 more Smart Citations